A method for evaluating the use of fluorescent dyes to track proliferation in cell lines by dye dilution. Issue 12 (25th October 2013) - Begum, Julfa; Day, William; Henderson, Carl; Purewal, Sukhveer; Cerveira, Joana; Summers, Huw; Rees, Paul; Davies, Derek; Filby, Andrew
Abstract Labeling nonquiescent cells with carboxyfluorescein succinimidyl ester (CFSE)‐like dyes gives rise to a population width exceeding the threshold for resolving division peaks by flow cytometry. Width is a function of biological heterogeneity plus extrinsic and intrinsic error sources associated with the measurement process. Optimal cytometer performance minimizes extrinsic error, but reducing intrinsic error to the point of facilitating peak resolution requires careful fluorochrome selection and fluorescent cell sorting. In this study, we labeled the Jurkat and A549 cell lines with CFSE, CellTraceViolet (CTV), and eFluor 670 proliferation dye (EPD) to test if we could resolve division peaks in culture after reducing the labeled input widths by cell sorting. Reanalysis of the sorted populations to ascertain the level of reduction achieved always led to widths exceeding the gated limits due to the contribution of errors. Measuring detector‐specific extrinsic error by sorting uniform fluorescent particles with similar spectral properties to the tracking dyes allowed us to determine the intrinsic error for each dye and cell type using a simple mathematical approach. We found that cell intrinsic error ultimately dictated whether we could resolve division peaks, and that as this increased, the required sort gate width to resolve any division peaks decreased to the point whereby issues with yield made A549 unsuitable for this approach. Finally, attempts to improve yields by setting two concurrent sort gates on the fluorescence distribution enriched for cells in different stages of the cell cycle that had nonequivalent proliferative properties in culture and thus should be practiced with caution. © 2013 International Society for Advancement of Cytometry